Formulation of Heat-Induced Whey Protein Gels for Extrusion-Based 3D Printing - Valeska F. Sager; Merete B. Munk; Mikka Stenholdt Hansen; Wender L. P. Bredie; Lilia Ahrné (Foods, 2020)
This study investigated the extrusion-based 3D printability of heat-induced whey protein gels as protein rich food inks. In particular, the effects of ionic strength by the addition of NaCl (0–250 mM), protein content (10%, 15%, 20%), fat content (0%, 10%), and partial substitution of whey protein isolate (WPI) with microparticulated whey protein (MWP) or micellar casein isolate (MCI) on printability were assessed. Texture analysis, specifically Young’s modulus, rheological measurements including yield stress, and creep–recovery behavior were used to characterize the gels. Modifications of the formulation in terms of ionic strength, increased protein content, and the formation of emulsion gels were insufficient to maintain a continuous extrusion process or shape stability after printing. However, the substitution of WPI with MWP created more viscoeleastic gels with improved printability and shape retention of the 3D cube structure after deposition. The partial replacement of WPI with MCI led to phase separation and 3D-printed cubes that collapsed after deposition. A narrow range of rheological material properties make WPI and MWP emulsion gels promising food inks for extrusion-based 3D printing.